2019
DOI: 10.1186/s12882-019-1637-y
|View full text |Cite
|
Sign up to set email alerts
|

Management of anticoagulation and antiplatelet therapy in patients with primary membranous nephropathy

Abstract: BackgroundIt has been recognized that primary membranous nephropathy (MN) is related to an increased risk for thromboembolic complications. However, the current evidence supporting prophylactic and therapeutic anticoagulation is too weak to better meet the clinical needs of this patient population. The present review provides some suggestions to guide the decision on anticoagulant management in primary MN patients with a high risk of thrombosis or with thromboembolic complication.Materials and methodsWe extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 64 publications
(84 reference statements)
0
6
0
1
Order By: Relevance
“…The optimal strategy of antiplatelet and anticoagulation therapy following TAVR for stroke risk reduction and prevention or treatment of leaflet thrombosis also remains a point of debate. Antiplatelet therapies developed to help prevent thrombotic events ( 51 ) are not yet known because of wide variations in clinical practice and heterogeneous trial populations. It is also not known whether thromboembolic complications and leaflet thrombosis following TAVR occur predominantly because of platelet- or thrombin-mediated clot formation, which could also alter the strategy of anticoagulation post-procedure ( 52 ).…”
Section: Platelets and Bioprosthetic Valvesmentioning
confidence: 99%
“…The optimal strategy of antiplatelet and anticoagulation therapy following TAVR for stroke risk reduction and prevention or treatment of leaflet thrombosis also remains a point of debate. Antiplatelet therapies developed to help prevent thrombotic events ( 51 ) are not yet known because of wide variations in clinical practice and heterogeneous trial populations. It is also not known whether thromboembolic complications and leaflet thrombosis following TAVR occur predominantly because of platelet- or thrombin-mediated clot formation, which could also alter the strategy of anticoagulation post-procedure ( 52 ).…”
Section: Platelets and Bioprosthetic Valvesmentioning
confidence: 99%
“…Already in the early 1980s it was noted that the risk of a venous thrombotic event (VTE) and associated pulmonary embolism was particularly high in patients with nephrotic syndrome (NS) due to primary MN. VTEs including deep venous thrombosis, renal vein thrombosis, and pulmonary embolism are recognized as early complications of primary MN that carry significant morbidity and mortality [76, 77]. A European study [78] has found that clinically apparent venous thromboembolic events occur in about 7% of patients with MN.…”
Section: Thrombotic Events In Mn and Its Managementmentioning
confidence: 99%
“…Next to VTE, patients with NS might also be at risk of arterial thrombotic events (ATEs). The primary cardiovascular events (CVEs) included acute coronary syndrome and ischemic stroke [76, 77]. In the study by Lee et al, the morbidity of CVEs was 4.4, 5.4, 8.2, and 8.8% at 1, 2, 3, and 5 years, respectively, in a primary MN cohort [81].…”
Section: Thrombotic Events In Mn and Its Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…MN is often accompanied by the existence of hypercoagulability and hyperviscosity, which is prone to thrombosis, embolism, and other complications, promoting microcirculation disorders and accelerating the occurrence of glomerulosclerosis and renal fibrosis. Therefore, some experts have suggested that promoting blood circulation, removing stasis, and anticoagulation should be considered throughout the treatment of MN (Zou et al, 2019).…”
Section: Introductionmentioning
confidence: 99%